The influence of connection stiffness on the dynamic properties and seismic performance of tall cross-laminated timber buildings. (1st July 2021) - Zhang, Xiaoyue; Pan, Yuxin; Tannert, Thomas
Highlights: Two balloon-type tall CLT buildings are designed for Vancouver, Canada. 22 building models are developed with different stiffness variations of connections. Modal analyses quantify the changes of building period and stiffness. Time history analyses evaluate the impact of connections on drift and base shear. The influence of connection stiffness decreases with the increase of building height. Abstract: It has become common practise to use Cross-laminated Timber (CLT) panels in shear wall applications in buildings around the world. Herein, the influence of the hold-downs, vertical and horizontal shear connections between the CLT panels on the period and stiffness of buildings was investigated. Two prototypes, 12-storey and 18-storey tall, of balloon-type construction were designed. To address the local seismicity of the chosen site in Vancouver, Canada, a range of crustal, subcrustal and subduction ground motions was selected for assessment as per the 2015 National Building Code of Canada. A total of 22 three-dimensional finite element building models with different combinations of connection properties were developed. Modal and time history analyses showed that the horizontal connections have the most significant impact on the overall building stiffness, resulting in up to 47% lager drifts when compared to the baseline model with an assumed rigid connection. The hold-down and vertical connection stiffnesses have lower impact on the dynamic properties and seismic performance of tall CLT buildings. The influence of connection stiffness was found to decrease with the increase of building height for this particular CLT tall building system with the connections designed as in this research.